Assessing the Significance of Industrial Heritage: The Case of Volos, Greece. (3rd July 2022) - Dimitriou, Maria
ABSTRACT: This article summarises the assessment of industrial heritage in Greece and revisits the remains of Glavanis Ironworks in Volos, shedding new light on the significance of this remarkable industrial building. It employs a value-based approach as a methodology, involving the documentation of surviving industrial buildings as well as the analysis of unpublished archival data. The detailed examination of Glavanis Ironworks illustrates how under-represented, derelict and at-risk industrial structures can provide evidence for overlooked industrial heritage values.